EXPLORING THE DEVELOPMENT OF PROCEDURAL KNOWLEDGE AND RELATED COMPETENCIES THROUGH STUDY OF BIOLOGY IN MIDDLE AND HIGH SCHOOLS IN ROMANIA - Miriam KENYERES; Ion ALBULESCU; Irina POP-PĂCURAR (Studia Universitatis Babes-Bolyai, 2022)
The current educational paradigm implemented worldwide is the development of competence comprising knowledge, skills, and attitudes. This research aims to investigate the acquisition of procedural knowledge and competencies targeting this type of knowledge through the study of Biology in middle and high schools in Romania. The paper first provides a brief overview of the history and existent usage of the concepts of competence and procedural knowledge. Moreover, it describes the Romanian educational system from a diachronic perspective. Following this, a careful analysis of middle and high school Biology syllabi is conducted. Particularly, development of procedural knowledge and competencies targeting procedural knowledge in these documents is examined critically. The results of this analysis indicate that, even though syllabi mention competence and procedural knowledge, they need more concrete activity guidance and assessment to train them. Finally, an online survey targeting high school ninth-graders and first-year university students is applied and analyzed. The survey assesses the implementation of instruction based on procedural knowledge. The results reveal the need for more logistics (laboratories and instruments) provision in schools and for carrying out practical activities. A need for reconsidering Biology syllabi, educational investment, and teacher preparation is necessary to succeed in developing procedural knowledge and competencies associated with this, through the study of Biology.